Faktor Penentu Kebijakan Cash Holding Pada Perusahaan Consumer Goods Di Indonesia - Erico Theonaldo, Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2022)
This research was conducted with the aim of empirically examining the effect of cash flow, leverage, net working capital, growth opportunity, and board size on cash holding in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. Samples were obtained using purposive sampling method. The total population in this study were 31 consumer goods companies on the Indonesia Stock Exchange (IDX). Data processing is done by using Eviews 10. The results showed that net working capital had a negative effect on cash holding, while cash flow, leverage, growth opportunity, and board size had no effect on cash holding. The implication of this research is that companies and investors need to observe to the company's net working capital because it will affect the company's cash holding.